1998
DOI: 10.1017/s002221510014246x
|View full text |Cite
|
Sign up to set email alerts
|

A clinic for the rapid processing of patients with neck masses

Abstract: Neck masses are common and may have serious underlying pathology. There is much anxiety and confusion in primary care as to which hospital department will provide the patient with the best service and the swiftest diagnosis. A clinic was set up at Wexham Park hospital to enable patients with neck masses to be seen early, and to undergo a one-stop specialist evaluation, ultrasound scan and fine needle aspiration biopsy. The clinic has yielded a wide variety of benign and malignant pathology. The first 100 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Recent papers have shown the benefits of a dedicated neck lump clinic [21][22][23][24][25] and found that neck nodes represented the commonest single reason for referral. Nodes accounted for 46 of 100 consecutive neck lumps in one study 25 and 43 of 110 in a second study, 26 but neither paper presented the context of pre-existing care in the absence of such a service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers have shown the benefits of a dedicated neck lump clinic [21][22][23][24][25] and found that neck nodes represented the commonest single reason for referral. Nodes accounted for 46 of 100 consecutive neck lumps in one study 25 and 43 of 110 in a second study, 26 but neither paper presented the context of pre-existing care in the absence of such a service.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] There have also been reports on the value of generic neck lump clinics. [21][22][23][24][25] The scale and nature of the problem of referral and management of patients with enlarged superficial lymph nodes, both those in the neck or elsewhere, has however not been closely investigated. We, therefore, examined the records of all patients who underwent superficial lymph node biopsy in our hospital over a 3-year period in order to characterise: (i) the patterns of referral from primary to secondary care; and (ii) the patient's pathway of care from the time of referral to being informed of a diagnosis.…”
mentioning
confidence: 99%
“…The original systematic review by Gagliardi et al 12 included twenty articles that described outcomes related to specific disease-site assessment units: eleven for breast cancer 4,[15][16][17][18][19][20][21][22][23][24] , three for colorectal cancer 7,25,26 , and six for head-and-neck cancer [31][32][33][34][35][36] . There were seventeen case series that involved 38-3119 patients, two rcts that included 478 and 791 patients, and one case-control study that included 177 cases and 162 controls 4,7,[15][16][17][18][19][20][21][22][23][24][25][26][31][32][33][34][35][36] .…”
Section: Search Resultsmentioning
confidence: 99%
“…There were seventeen case series that involved 38-3119 patients, two rcts that included 478 and 791 patients, and one case-control study that included 177 cases and 162 controls 4,7,[15][16][17][18][19][20][21][22][23][24][25][26][31][32][33][34][35][36] . The update of the literature search identified 823 citations in which patient outcomes related to diagnostic assessment units were described for colorectal cancer in four studies [27][28][29][30] , head-and-neck cancer in two studies 37,38 , lung cancer in two studies 39,40 , gynecologic cancers in three studies [41][42][43] , neurologic cancers in one study 44 , lymph node cancers in one study 45 , and upper gastrointestinal cancers in one study 46 .…”
Section: Search Resultsmentioning
confidence: 99%
“…19 Reviews of other multi-disciplinary clinics have found them to be an effective way of dealing with complex problems with multiple underlying aetiologies and simplifying the patient's diagnostic pathway. [20][21][22] The case studies clearly illustrate that patients with atypical presentations of neurodegenerative disease with or without exacerbating concomitant eye pathology frequently visited many clinics before reaching a diagnosis. The aim of the Visual Perception Clinic is to prevent this continuing re-referral by acting as a one-stop service where comprehensive evaluation may be made and a representative diagnosis given.…”
Section: Discussionmentioning
confidence: 99%